Amino Acid Substitutions of MagA in Klebsiella pneumoniae Affect the Biosynthesis of the Capsular Polysaccharide - Lin, Tzu-Lung (Public Library of Science, 2012)
Mucoviscosity-associated gene A (magA) of Klebsiella pneumoniae contributes to K1 capsular polysaccharide (CPS) biosynthesis. Based on sequence homology and gene alignment, the magA gene has been predicted to encode a Wzy-type CPS polymerase. Sequence alignment with the Wzy_C and RfaL protein families (which catalyze CPS or lipopolysaccharide (LPS) biosynthesis) and topological analysis has suggested that eight highly conserved residues, including G308, G310, G334, G337, R290, P305, H323, and N324, were located in a hypothetical loop region. Therefore, we used site-directed mutagenesis to study the role of these residues in CPS production, and to observe the consequent phenotypes such as mucoviscosity, serum and phagocytosis resistance, and virulence (as assessed in mice) in pyogenic liver abscess strain NTUH-K2044. Alanine substitutions at R290 or H323 abolished all of these properties. The G308A mutant was severely impaired for these functions. The G334A mutant remained mucoid with decreased CPS production, but its virulence was significantly reduced in vivo. No phenotypic change was observed for strains harboring magA G310A, G337A, P305A, or N324A mutations. Therefore, R290, G308, H323, and G334 are functionally important residues of the MagA (Wzy) protein of K. pneumoniae NTUH-K2044, capsular type K1. These amino acids are also likely to be important for the function of Wzy in other capsular types in K. pneumoniae and other species bearing Wzy_C family proteins.